PERFORMANCE OF NEW MID LATE SUGARCANE GENOTYPES UNDER DIFFERENT NITROGEN LEVELS IN NORTH COASTAL ZONE OF ANDHRA PRADESH - V , GOURI (The Journal of Research ANGRAU, 2026)
A field experiment was conducted at Regional Agricultural Research Station farm, Anakapalle with an objective to determine ideal amount of nitrogen requirement for mid-late Sugarcane genotypes during the year 2024-25. Three new sugarcane genotypes viz.,2015A230 (CoA20325), 2015A233 (CoA20326),2015A93(CoA ) along with check variety 2009A252 (CoA14323) were tested at four nitrogen levels viz., FYM @ 25 t ha-1 + 100% recommended dose of Nitrogen (F1), FYM @ 25 t ha-1+ 125% recommended dose of Nitrogen (F2), FYM @ 25 t ha-1 + 150% recommended dose of Nitrogen (F3) and application of 100% recommended dose of Nitrogen + In situ incorporation of sunhemp sown as intercrop (F4). The recommended dose was 168 kg N ha-1. The trial was conducted in Factorial RBD with three replications. The findings of the study showed that, the genotypes 2015A233 (85.6 t ha-1) and 2015A230 (82.1 t ha-1) recorded considerably greater cane yield in comparison to the other genotype 2015A93(77.7 t ha-1) and check variety 2009A252 (79.2 t ha-1). Among the four nitrogen levels new mid late sugarcane genotypes produced superior cane yield with application of FYM @ 25 t ha-1+150% RDN (84.3 t ha-1) and 100% RDN + Sunhemp grown as intercrop and in situ incorporation (83.4 t ha-1). Application of FYM @ 25 t ha-1+100% Recommended dose of Nitrogen recorded significantly lower cane yield of 76.9 t ha-1. There was no difference in the juice quality parameters for different treatments, however 2015A233 recorded high sucrose percent of 18.8. Among nitrogen levels, application of 100% RDN + Sunhemp grown as intercrop and in situ incorporation recorded high sucrose percent of 18.1.